Relationship between female employees and firm’s innovation: Evidence from Japanese companies - Taro Ichikawa; Mika Goto (PLoS ONE, 2025)
This study investigates how female employees contribute to firm innovation by applying panel data Poisson regression models to data pertaining to 144 major Japanese manufacturing firms from 2004 to 2022. The results reveal the following: First, there is a positive relationship between longer female employment and innovation. Longer female employment may be attributable to female employees feeling more secure at their workplaces. Second, regarding women’s unique perspectives, this study suggests that female participation in innovation may increase the number of technological fields. Third, this study presents the mediating effects of technological fields on the relationship between high-impact innovation and the demographic of female employees. These findings suggest corporate management creates a system that allows female employees to play an active role in the workplace with long-term employment. The empirical results provide new insights into previous literature on corporate innovation, specifically technological innovation.